SENI GERAK DAN TARI DI YAYASAN PENDIDIKAN PAUD/RA ISLAM NURUL ARAFAH - Elfina Yanti; Hilda Zahra; Indah Afrilia; Ririn Widayanti (JIP: Jurnal Ilmu Pendidikan, 2025)
Movement and dance art are essential components of early childhood education, aiming to stimulate children’s motor, social, emotional, and spiritual development. This study was conducted at the Islamic Early Childhood Education Foundation (PAUD/RA) Nurul Arafah to examine the role and impact of movement and dance activities on children’s development in the context of Islamic education. The research was motivated by the importance of integrating Islamic values into early childhood art education, which is often underappreciated. The method used was qualitative descriptive with a case study approach. Data were collected through observation, interviews with teachers and parents, and documentation of art learning activities. The findings indicate that movement and dance activities conducted routinely and integrated with Islamic values can enhance gross motor, cognitive, language, social-emotional development, and religious character formation. These activities also improve children's active participation in learning and strengthen emotional bonds between teachers and students. This study suggests that movement and dance art serve not only as entertainment but also as an effective educational strategy for value-based early childhood development. The conclusion highlights the need for strengthening teacher training in Islamic arts and providing better facilities in Islamic early childhood education institutions.